THE ROLE OF TEACHER STUDENT TRADITIONS IN EPIC SCHOOLS - Rakhimova Maysara Bakhtiyor qizi (Journals Park Publishing, 2022)
Annotation. In this article, you can learn enough about the role of teacher-student traditions in epic schools.
Keywords: epic schools; teacher-student traditions; “Alpomish